The Mesopotamian Context of Ezekiel - Bodi, Daniel 1956- (2020)
The book of Ezekiel explicitly locates its material in Babylon between the years 593 and 571 BCE. The book’s language and imagery correspond to that setting. This chapter surveys the rich research of the book’s Mesopotamian context in three areas: comparative cultural elements, iconography and imagery, and philological research. The abundance of the evidence demonstrates that the prophet’s activity took place mainly in Babylonia, influencing the language, metaphors, content, and rich imagery of the book that bears his name and is essential for reconstructing the book’s composition.
Keywords: Ezekiel; Babylonian Exile; Akkadian; Aramaic; Iconography; Mesopotamia; Assyria; Babylon